Innovation in producing virgin coconut oil without heating in Pekon Bumiratu, Pringsewu - Aspita Laila; Yuli Ambarwati; John Hendri; M Setyarini; Syaiful Bahri (Community Empowerment, 2024)
Among the various potential gardens in Pekon Bumiratu, Pagelaran District, Pringsewu Regency, coconut plants stand out. However, the processing of coconut produce by farmers is suboptimal, as the coconut yield is typically consumed or sold without undergoing processing. This is primarily due to the limited knowledge and skills of local farmers regarding coconut processing and its derivatives. This activity aims to enhance the knowledge and skills of coconut farmers in processing coconuts into Virgin Coconut Oil (VCO) using a non-heating method. The activities involved a combination of lecture methods and practical demonstrations. The VCO produced during the activities underwent laboratory analysis to assess its quality. The results of the activity indicate a significant increase in understanding by 61.6%. This suggests a substantial improvement in public knowledge regarding the processing of coconuts into VCO. Laboratory analysis of the VCO produced by the participants revealed a water content of 0.18%, an iodine value of 8,150 g iod/100g, a free fatty acid content of 0.17%, and a peroxide value of 1.32 mg/Kg Ek. These results align with the quality standards outlined in SNI 7381-2008 for VCO.